Pendidikan Lingkungan Melalui Sekolah Alam Edukasi Mangrove di Literasi Pesisir Dusun Cemare - Nabila, Hesti; Napsita, Dian; Anggraini, Eva; Sulistianawati, Nadia Evi; Deayantika, Ni Nengah Cindy Sri; Safitri, Ila; Santoso, Didik; Lestari, Tri Ayu (Universitas Mataram, 2025)
Mangrove forests play an important role in protecting the coast from abrasion, providing habitat for marine life, and sequestering carbon. However, mangroves are threatened by land conversion, unsustainable activities, and lack of public awareness. This program aims to build a generation that cares about the environment and encourages active community involvement in coastal conservation. This approach is expected to create a generation that not only has environmental knowledge, but also has the care and skills to contribute to conservation efforts. The program began with field observations and interviews to collect data on the geographical conditions and understanding of the local community regarding mangrove ecosystems. The results of observations were used to design teaching media in the form of mangrove species identification books, books about mangrove ecosystems, animal association books in mangroves, and educational games about food chains in mangroves. Based on the results of the activities, this study shows that the use of teaching media in the form of mangrove food chain posters, pictures of mangrove ecosystem fauna, and books about mangrove species is effective in increasing children's knowledge about mangrove ecosystems.